2018
DOI: 10.7759/cureus.2666
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Eyebrow Hypotrichosis with Bimatoprost 0.03% Solution: Case Report and Literature Review

Abstract: The eyebrows frame the upper margin of the orbit and are an essential feature of the facial landscape. Eyebrow hypotrichosis, also known as madarosis, is characterized by a lack of growth or loss of eyebrow hair. Eyebrow loss can have cosmetic, functional, and social consequences. Eyebrow hypotrichosis can be idiopathic or related to an underlying condition. Bimatoprost 0.03% solution is a prostamide F2α analog indicated for the treatment of glaucoma and ocular hypertension that has also demonstrated efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Improvement in eyebrow hypotrichosis in this clinical trial is consistent with previous studies. Both concentrations provided significantly greater improvement in eyebrow growth compared to baseline, without serious side effects …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Improvement in eyebrow hypotrichosis in this clinical trial is consistent with previous studies. Both concentrations provided significantly greater improvement in eyebrow growth compared to baseline, without serious side effects …”
Section: Discussionmentioning
confidence: 90%
“…Bimatoprost 0.03% was accidentally found to cause eyelash hypertrichosis as an adverse effect among glaucoma patients, leading to approval by the United States Food and Drug Administration (FDA) as a treatment of eyelash hypotrichosis . Subsequently, the 0.03% formulation has been experimented in various clinical studies of eyebrow hypotrichosis, including four case reports and four randomized controlled trials, which revealed the efficacy and safety of this concentration in enhancing eyebrow growth …”
Section: Introductionmentioning
confidence: 99%
“…As examples, the growth rate of the tiny hairs of eyebrows, their respective durations of growth/arrest phases (Anagen, Telogen) have not been investigated, up to our knowledge. In some clinical rare cases, a strong rarefaction of hairs (hypotrichosis) can be observed .…”
Section: Introductionmentioning
confidence: 99%
“…Tel. : +33 149795334; fax: +33 149795142; e-mail: frederic.flament@rd.loreal.com rare cases, a strong rarefaction of hairs (hypotrichosis) can be observed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation